A Dominant Alarm Symptom in Eldery Patient with Gastroduodenitis Erosive NSAID - Yudi Agung Wibisono; Harijono Achmad (The Indonesian Society for Digestive Endoscopy, 2005)
Alarm symptoms for dyspepsia, such as anemia, evidence of gastrointestinal bleeding, weight loss, dysphagia, odynophagia and new onset at age 50 years are associated with an increase risk of cancer. Most guidelines for the management of dyspepsia emphasize that patients with alarm symptoms should undergo aggressive evaluation including endoscopy. We reported a case of 65 years old female with several alarm symptoms that suggesting of malignancy, but endoscopy finding revealed gastroduodenitis erosive NSAID due to the pain killer herbal medicine use. Keywords: melena, alarm symptoms, cancer, gastroduodenitis, NSAID